MEME SEBAGAI MEDIA PEMBELAJARAN PAI: ANTARA KREATIVITAS DAN HUMANIORA DIGITAL - Shafwan Aidinal Ma’arif (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
The development of digital culture presents both challenges and opportunities for innovation in educational media, particularly in the context of Islamic Religious Education (PAI). This article explores the potential of memes as creative and contextual educational tools for conveying Islamic values to the digital generation. Using a qualitative approach and Roland Barthes’ semiotic analysis, the study examines 50 religion-themed memes collected from Instagram, TikTok, and Twitter, supported by interviews with five PAI teachers who have integrated memes into their teaching practices. The findings reveal three key potentials of memes: first, simplifying abstract or complex religious concepts into more digestible content; second, increasing student engagement through visual and humorous approaches; and third, stimulating critical discussion on the interpretation of religious texts in contemporary contexts. Nevertheless, the use of memes also carries risks, such as excessive simplification of Islamic values, content that may offend the sanctity of religious symbols, and a generational gap in media literacy between teachers (digital immigrants) and students (digital natives). Therefore, the implementation of ethical frameworks and digital literacy strategies in Islamic education is essential, including teacher training and the development of an educational meme repository grounded in wasathiyah (moderate) Islamic values. Through a digital humanities lens, memes can serve not merely as entertainment, but as creative, reflective, and transformative pedagogical bridges.